Analysis of contact and tooth geometry in internal spur gears and their influence on the resistance of said gears - Abregú Leandro, Edwin Asención (2008)
Internal spur gears have their particularities with respect to external spur gears in terms of their geometry, contact characteristics and duration of the same. These gears are subject to the same types of failures as external spur gears, although as a result of tooth geometry and shape, these failures are less frequent than external spur gears. In the present work, a study of the particular characteristics of the contact in the internal spur gears is made, analyzing aspects such as: contact tensions, coating coefficient and influence of the correction of the toothing in the reduction of the failures of these gears.